ANALISIS ACTIVE FIRE PROTECTION SYSTEM APAR DAN HIDRAN DI AREA OG FIELD PT. XYZ TAHUN 2022 - Husen, Husen; Yunita, Yunita; Sahuri, Sahuri; Siddique, Faris (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2022)
Fires have a very broad hazard impact, which includes social and economic impacts, so it is necessary to be prepared to deal with fires. The existence of an active fire protection system is one form of effort for early prevention and mitigation of potential fire hazards. The purpose of this study was to determine the suitability of the inspection program, inspection procedures and implementation or application of fire extinguishers and hydrants in the OG Field area of PT. XYZ with PerMenNaKerTrans No. 4 of 1980, SNI-03-1745-2000, NFPA 10 of 2013 and NFPA 25 of 2014. The type and research design used is a qualitative method, with a descriptive research design using a comparative approach. The population in this study were all workers in the OG Field area of PT. XYZ with a number of workers as many as 248 people, then it is determined 20 informants including 2 key informants. Data collection techniques through direct observation or survey in the OG Field area of PT. XYZ and conduct interviews. Based on the results of observations and interviews that the author has done, the area of OG Field PT. XYZ already has an inspection program, inspection procedures and implementation or application of fire extinguishers and hydrants in accordance with PerMenNaKerTrans No. 4 of 1980, SNI-03-1745-2000, NFPA 10 of 2013 and NFPA 25 of 2014. However, there are still discrepancies in the hydrotest or hydrostatic testing of the fire extinguisher tube, instructions for use or operation of the fire extinguisher, placement of the fire extinguisher and damage or defects in the hydrant.